2021
DOI: 10.3390/antiox10111682
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Abrogates Oxidative Stress and Neuroinflammation after Cortical Stab Wound Injury

Abstract: Disruptions in brain energy metabolism, oxidative damage, and neuroinflammation are commonly seen in traumatic brain injury (TBI). Microglial activation is the hallmark of neuroinflammation. After brain injury, microglia also act as a double-edged sword with distinctive phenotypic changes. Therefore, therapeutic applications to potentiate microglia towards pro-inflammatory response following brain injury have become the focus of attention in recent years. Here, in the current study, we investigated the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…Similar to our findings, p53 was found to be activated in the ischemic areas of brain, which resulted in neuronal apoptosis [25] , and p53 loss or applications of p53 inhibitors significantly attenuated brain damage in several stroke models [26] . Furthermore, 17β-estradiol administration rescued p53-stimulated apoptotic cell death in the cortical stab wound injury model by modulating the expressions of Bax and Bcl-2 and caspase-3 activation [27] . However, the specific role of p53 in SENP5-mediated TBI progression needs to be further verified.…”
Section: Discussionmentioning
confidence: 91%
“…Similar to our findings, p53 was found to be activated in the ischemic areas of brain, which resulted in neuronal apoptosis [25] , and p53 loss or applications of p53 inhibitors significantly attenuated brain damage in several stroke models [26] . Furthermore, 17β-estradiol administration rescued p53-stimulated apoptotic cell death in the cortical stab wound injury model by modulating the expressions of Bax and Bcl-2 and caspase-3 activation [27] . However, the specific role of p53 in SENP5-mediated TBI progression needs to be further verified.…”
Section: Discussionmentioning
confidence: 91%
“…However, considering the effects of GPER treatment on Aβo-induced changes in [Ca 2+ ] i , it is unlikely that the inhibitory effects of raloxifene and estradiol on Aβo-induced ROS production can be solely explained by mechanisms mediated by membrane GPER stimulation. It has been reported that raloxifene or estradiol increase the expression of Glutathione-SH, an antioxidant in cells [ 43 , 44 ]. Based on these previous studies, the increased expression of antioxidants, including Glutathione-SH, by raloxifene or estradiol may be caused by the stimulation of GPER, which is expressed in intracellular organelles such as mitochondria and the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 also regulates the expression several antioxidants defense genes through several mechanism, including HO-1, which removed the toxic heme, carbon monoxide, and iron ions. Additionally, HO-1 protects the cells against ROS and oxidative stress [ 72 , 73 ]. Furthermore, the natural bioactive supplements like vitamins play an important role against oxidative stress and neurodegeneration [ 74 ].…”
Section: Discussionmentioning
confidence: 99%